Chylothorax Complicating Closure of the Ductus Arteriosus: The Second Case - L. Ennazk; O. Echouka; R. El Houati; Y. Mouaffak; G. El Adib; D. Boumzebra; S. Younous (Case Reports in Surgery)
Chylothorax is a possible complication of intrathoracic surgery. The diagnosis of postoperative chylothorax is easy; however, the treatment can cause problems of management because of the lack of consensus. In children, the most common causes of postoperative chylothorax are the cures for congenital heart diseases. We report the case of a two-year-old child, presenting with a chylothorax following surgery of the ductus arteriosus. Our case illustrates the treatment that must first include medical measures without delaying the surgery. The risk is the installation of nutritional and immune deficiency.